An innovative system for sharing, integration and visualization of heterogeneous 4D-information. (March 2016) - Paciello, R.; Coviello, I.; Bitonto, P.; Donvito, A.; Filizzola, C.; Genzano, N.; Lisi, M.; Pergola, N.; Sileo, G.; Tramutoli, V.
Abstract: Treating the time dimension (i.e., the 4th dimension) of geospatial parameters, likewise the other dimensions is important for some applications to better understand the possible space-time relations among the physical parameters underlying the dynamics of complex phenomena. In this paper we present the potential of an innovative solution, named 4 Dimensions Environmental ObServation (4DEOS), which is a platform able to handle the 4th dimension in an asynchronous way (i.e., to visualize more signals, holding some of them fixed in the time domain while moving others over time). 4DEOS is based on a Client-Broker-Server architecture for the easy integration and visualization of heterogeneous, asynchronous, geospatial products. The prototype system was evaluated in the case of earthquake prediction studies where the asynchronous visualization of independent observations could allow a timely identification of the spatial correlations appearing at different time lags, which could be missed using other existing 4D Geographic Information System software. Highlights: 4DEOS visualizes and integrates heterogeneous observations in the space-time domain. 4DEOS users can move signals while holding the others fixed in the time domain. We verified the 4DEOS potentiality during the EC-FP7 PRE-EARTHQUAKES project.